Analisa Teknikal MACD, RSI, SO, dan Buy and Hold untuk Mencapai Return Optimal Saham JII30 di Bursa Efek Indonesia - Norma Rosyidah; Resandi Umami Hafi (The Indonesia Capital Market Institute, 2021)
The purpose of this research is to realize the movement of JII 30 shares during the pandemic. The method used is a descriptive analysis by analyzing this research to find that JII 30 stocks, particularly in the banking sector, take a fairly high level of fluctuation. indecision from the pandemic situation caused the banking sector to increase, thus affecting stock trading. The results of this study to indicate the novelty of this study are the movement of stocks through the pandemic, which is different from earlier studies that still studied when trading was normal / before the pandemic. MACD, RSI, SO and Buy and Hold analysis tools can generate optimal returns on BTPS shares. The limitations of this research are still limited to the Islamic banking sector.